2020
DOI: 10.3168/jds.2020-18349
|View full text |Cite
|
Sign up to set email alerts
|

Using lactic acid bacteria and packaging with grapefruit seed extract for controlling Listeria monocytogenes growth in fresh soft cheese

Abstract: Various cheese products are involved in outbreaks of listeriosis worldwide due to high consumption and prolonged refrigerated storage. The objective of this study was to determine the efficacy of using lactic acid bacteria and packaging with grapefruit seed extract (GSE) for controlling Listeria monocytogenes growth in soft cheese. Leuconostoc mesenteroides and Lactobacillus curvatus isolated from kimchi were used as a starter culture to make a soft cheese, which was inoculated with a cocktail strain of L. mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Other results were obtained by Lim et al (2020), who also studied the effects of LAB mixtures on the survival of L. monocytogenes. The Lim et al (2020) study investigated the effect of LAB such as of Leu. mesenteroides and Lb.…”
Section: Discussionmentioning
confidence: 87%
“…Other results were obtained by Lim et al (2020), who also studied the effects of LAB mixtures on the survival of L. monocytogenes. The Lim et al (2020) study investigated the effect of LAB such as of Leu. mesenteroides and Lb.…”
Section: Discussionmentioning
confidence: 87%
“…Polyphenols can not only increase the permeability of the cell membrane and cause energy metabolism inhibition but also interfere with the growth and reproduction of microorganisms (Liu et al, 2020). Similarly, Lim et al (2020) found that the packaging lms of GSE can also better delay the growth of L. monocy-togenes in soft cheese. Qin et al (2019) found that the addition of Lycium ruthenicum Murr to cassava starch could inhibit meat product oxidation, and among them mainly is the effect of anthocyanins.…”
Section: Antimicrobial Activity Of Cs/кc -Gse Lmsmentioning
confidence: 96%
“…Alternatively, active packaging systems are a promising approach to extend the efficacy of antimicrobial agents by reducing their interactions with food components and controlling their release on the cheese . Lim et al reported significant growth inhibition of L. monocytogenes on fresh cheese samples, stored at 10 and 15 °C, when both Leuconostoc mesenteroides (protective culture) and a packaging film containing grapefruit seed extract were applied; however, cheeses with only protective culture or only active packaging showed limited efficacy to control the growth of the pathogen.…”
Section: Postprocessing Technologymentioning
confidence: 99%